2014
DOI: 10.1161/jaha.114.001220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heme and Heme Degradation Products on Vascular Diameter in Mouse Visual Cortex

Abstract: BackgroundDelayed cerebral vasospasm is the most common cause of mortality and severe neurological impairment in patients who survive subarachnoid hemorrhage. Despite improvements in the field of diagnostic imaging, options for prevention and medical treatment—primarily with the calcium channel antagonist nimodipine or hemodynamic manipulations—are insufficient. Previous studies have suggested that heme and bilirubin oxidation end products, originating from degraded hemoglobin around ruptured blood vessels, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…Moreover, we further used the BKCa channel blocker paxilline and found that, regardless of whether it was used before or after CCCP treatment, it had no significant effect on CCCP-induced vasorelaxation in endothelium-denuded rat mensenteric arteries (data not shown). Paxilline at 1 μM has been shown to inhibit vasodilatation in arterioles (Joerk et al, 2014), but we observed no effect on CCCP-induced vasorelaxation even with 5 μM, indicating that the BKCa channel is not involved in the CCCP-induced vasorelaxation.…”
Section: Cccp Activates Ampk In Vascular Smooth Muscle Cells and Rat contrasting
confidence: 74%
“…Moreover, we further used the BKCa channel blocker paxilline and found that, regardless of whether it was used before or after CCCP treatment, it had no significant effect on CCCP-induced vasorelaxation in endothelium-denuded rat mensenteric arteries (data not shown). Paxilline at 1 μM has been shown to inhibit vasodilatation in arterioles (Joerk et al, 2014), but we observed no effect on CCCP-induced vasorelaxation even with 5 μM, indicating that the BKCa channel is not involved in the CCCP-induced vasorelaxation.…”
Section: Cccp Activates Ampk In Vascular Smooth Muscle Cells and Rat contrasting
confidence: 74%
“…Such vasoconstriction is counteracted by nitric oxide (NO) that inhibits ET-1 release, resulting in vasodilation 156. Iron-containing haem has been shown to cause vasoconstriction 157. Indeed, reductions in free-iron levels ameliorate SAH-induced vasosconstriction 158.…”
Section: Subarachnoid Haemorrhagementioning
confidence: 99%
“…Bilirubin oxidation end products (BOXes) increasingly attract attention because they are suspected to play an important role in delayed cerebral vasospasm after subarachnoid hemorrhage [1][2][3]. In the course of blood clotting and hemolysis large amounts of hemoglobin are liberated.…”
Section: Introductionmentioning
confidence: 99%